Finite element-based analysis of buckling-induced plastic deformation. (December 2021) - Žák, Stanislav; Lassnig, Alice; Cordill, Megan J.; Pippan, Reinhard
Abstract: In recent years, the investigation of adhesion properties of thin films on brittle substrates is receiving more attention due to the spread of thin film applications (coatings, protective layers, conductive layers in microelectronics, etc.). However, a basic approach for adhesion measurements proposed by Hutchinson and Suo almost three decades ago is still widely used due to its easy applicability. This approach uses thin film spontaneous buckling using residual compressive stresses in the film, however, it is based on Euler beam theory and accounts only for elastic behavior. Modern material combinations may lead to permanent plastic deformations, even under the controlled experimental conditions according to the elastic model. This work aims at investigating the plastic deformation influence on the experimental procedure according to Hutchinson and Suo by the means of the finite element analysis on the specific Mo-Cu-glass system. The deformations of spontaneously formed buckles are compared between purely elastic, (more realistic) elastic-plastic model and previously published experimental results together with quantification of the dissipated energy via the current finite element model. The comparison of the two numerical approaches shows non-negligible plastic deformations of the spontaneously formed buckles which has an effect on the film deformed shape (corresponding to the experimental observations) as well as on the portion of the shear loading at the delamination crack tip. This indicates that the plastic deformation during the buckling delamination may have some impact on the stability of the delamination crack.